IMĀM ABŪ HASAN AL-ASY‘ARĪ: ANALISA BERHUBUNG SUMBANGAN TAJDID DAN ISLAHNYA - Berahim@Ibrahim, Ahmad Zaki (Journal of Al-Tamaddun, 2010)
Al-Imām Abū Hasan al-Asy'arī (883-935 M) is one of the Mujaddid Muslims. Through his efforts and dedication in debate, writing and preaching, Muslim community has been able to return to the purity of the faith, appreciating Islamic and ethical life in the Muslim community in facing attacks by those who use rational approach to waive the notion of the Qur'an and Sunnah. This article attempts to briefly highlight the contribution and role of Abū Hasan al-Asy'arī to take lessons in dealing with issues of religious abuse. He started the role as reformers by showing the example which he repentance from deviant thought, followed later by his hard work in addressing corruption through dialogue, writing and preaching, and ultimately laid the foundations of Sunni's theology. Through this, Abū Hasan al-Asy'arī sets out an argument and analysis based on the Qur'an and Sunnah as well as using reason to encounter the rational mind by the Mu'tazili leaders. In fact the Qur'an has a large number of sentences referring to reasoning arguments in defining truthful and falsehood. From Abū Hasan al-Asy'arī, Sunni's theology was born. He took ulūhiyyah faith-based education approach based on twenty-attributes of Allah and he meet the basic application form of repentance for wrong thinking.